Правова природа корпоративних прав - Сосула, Олександр; Sosula, Alexander; Сосула, Александр (Видавництво Львівської політехніки, 2018)
Розглянуто проблематику правової природи корпоративних відносин. Досліджено декілька підходів щодо сфери існування корпоративного права та корпоративних правовідносин, а саме: теорію “комплексного правовідношення”; теорію “підприємницького правовідношення” та теорію, згідно з якою корпоративні правовідносини є різновидом цивільних. Доведено, доцільність проведення класифікації за суб’єктами, звертаючи увагу, що усі відносини – це відносини щодо участі в товаристві.

The article deals with the problems of the legal nature of corporate relations. Several approaches to the scope of corporate law and corporate legal relations are investigated, namely: there is the theory of “complex legal relationships”; the theory of “business relationship” and the theory according to which, corporate legal relationships are a kind of civilian. Proved the expediency of classification by subjects, while paying attention to the fact that all relations are relations regarding participation in the community.

В статье рассмотрена проблематика правовой природы корпоративных отношений. Исследовано несколько подходов к сферы существования корпоративного права и корпоративных правоотношений, а именно: есть теория “комплексного правоотношения”; теория “предпринимательского правоотношения” и теория согласно которой, корпоративные правоотношения являются разновидностью гражданских. Доказано, целесообразность проведения классификации по субъектам, обращая внимание при этом, что все отношения - это отношения по участию в обществе.
Legal nature of corporate rights
Правовая природа корпоративных прав
Keywords: правова природа; корпорація; корпоративні права; корпоративні правовідносини; корпоративне право; суб’єктивне корпоративне право; legal nature; corporation; corporate rights; corporate legal relations; corporate law; subjective corporate law; правовая природа; корпорация; корпоративные права; корпоративные правоотношения корпоративное право; субъективное корпоративное право; УДК